Synthesis, characterization, and thermoanalytical study of aceclofenac of light lanthanides in the solid state (La, Ce, Pr, and Nd) - Souza, Adrian Santos de; Ekawa, Bruno [UNESP]; Carvalho, Claudio Teodoro de; Teixeira, José Augusto; Ionashiro, Massao [UNESP]; Colman, Tiago André Denck (Elsevier, 2020)
Lanthanide aceclofenac compounds were synthesized by the addition of lanthanide nitrate aqueous solution to aceclofenac–acetone solution. The compounds obtained in the solid state were characterized by thermal and spectroscopic studies, as well as by complementary x-ray diffraction data. The metal–ligand stoichiometric ratio was defined by simultaneous thermogravimetry and differential scanning calorimetry (TG-DSC) as [Ln(Acec)3·nH2O], where Ln represents the metal centre (La, Ce, Pr, or Nd) and Acec represents the ligand, with n = 4(La), 3(Ce), and 2.5(Pr, Nd). TG-DSC and Fourier transform infrared spectroscopy (FTIR) data also allowed for determination of the thermal behaviour and possible coordination modes between the metal and the ligand.
Keywords: Aceclofenaco; Lanthanide complexes; Pyrolysis; Synthesis; TG-DSC-FTIR